2020
DOI: 10.1186/s12981-020-00308-w
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the utility and interest in a point-of-care urine tenofovir test for adherence to HIV pre-exposure prophylaxis and antiretroviral therapy: an exploratory qualitative assessment among U.S. clients and providers

Abstract: Background: Real-time, objective measures of adherence to antiretroviral therapy (ART) and pre-exposure prophylaxis (PrEP) are needed to better assess adherence levels and to expedite clinical response for those with suboptimal adherence. Point-of-care tenofovir (POC-TFV) testing has been proposed as a solution to facilitate real-time antiretroviral adherence monitoring, but little is known about how health care providers, people living with HIV (PLWH) receiving ART, and people receiving PrEP will perceive POC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…25 Encouragingly, a qualitative study found that healthcare providers may be interested in implementing POC TFV testing to assess ART adherence, and PLHIV may be receptive to POC TFV testing if it were incorporated into care. 28 Other studies have found that people receiving TFV-based pre-exposure prophylaxis are interested in druglevel testing and that receiving drug-level feedback may motivate improved medication adherence. [50][51][52][53] Integrating POC VL and TFV adherence monitoring into a single client encounter may offer other benefits to clients, providers, health systems and society such as earlier identification of HIV drug resistance and prevention of unnecessary switches to second-line ART regimens, which in turn can prevent HIV transmission, reduce costs of care and improve health outcomes for PLHIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Encouragingly, a qualitative study found that healthcare providers may be interested in implementing POC TFV testing to assess ART adherence, and PLHIV may be receptive to POC TFV testing if it were incorporated into care. 28 Other studies have found that people receiving TFV-based pre-exposure prophylaxis are interested in druglevel testing and that receiving drug-level feedback may motivate improved medication adherence. [50][51][52][53] Integrating POC VL and TFV adherence monitoring into a single client encounter may offer other benefits to clients, providers, health systems and society such as earlier identification of HIV drug resistance and prevention of unnecessary switches to second-line ART regimens, which in turn can prevent HIV transmission, reduce costs of care and improve health outcomes for PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Routine real-time ART adherence monitoring may also be beneficial in motivating subsequent good adherence among PLHIV and improving engagement in care. 27 28 However, little is known about the effects of implementing POC TFV adherence testing among PLHIV.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these studies will evaluate the potential effects of integrating POC urine TFV testing into care with other POC tests, such as a POC VL test. A qualitative study of providers, PLHIV receiving ART, and people receiving PrEP in Seattle found that POC urine TFV testing was acceptable and potentially useful for better informed clinical decision-making (85).…”
Section: Point-of-care Testing For Adherence Monitoring In Hiv Carementioning
confidence: 99%
“…Real-time, objective measures of adherence for PrEP are essential to assess how and when people are taking medication, and to accelerate a clinical and/or other supportive response for those with inadequate adherence. 20 , 21 Quantifying and monitoring adherence to PrEP can identify those at risk of becoming lost to follow-up and therefore at greater risk of HIV infection, 22 those in need of additional layers of support to overcome barriers to PrEP (impending health insurance loss, harm reduction tools, logistical support such as tokens), and individuals who need enhanced adherence support (more frequent visits, pill boxes, smart pill bottles, etc.). Indeed, metrics of PrEP adherence were strongly associated with future loss to follow-up in a US demonstration project study.…”
Section: Introductionmentioning
confidence: 99%